Jabari jumps [book with audioplayer] - Cornwall, Gaia (VOX Books, 2017)
Jabari is definitely ready to jump off the diving board. He's finished his swimming lessons and passed his swim test, and he's a great jumper, so he's not scared at all. 'Looks easy, ' says Jabari, watching the other kids take their turns. But when his dad squeezes his hand, Jabari squeezes back. He needs to figure out what kind of special jump to do anyway, and he should probably do some stretches before climbing up onto the diving board. In a sweetly appealing tale of overcoming your fears, newcomer Gaia Cornwall captures a moment between a patient and encouraging father and a determined little boy you can't help but root for.